Vita Art Now 1989. - Sack, Steven (Johannesburg : Johannesburg Art Gallery, 1990)
Hlungwani, Jackson ; Sekoto, Gerard ; Mendel, Gideon ; McCann, Mike ; Coetzee, Neels ; Dicks, Trudi ; Goldblatt, David ; Grobler, Diek ; Gazland, Hlungwane ; Hobbs, Philippa ; Koloane, David ; Kumalo, Alf ; Legae, Ezrom ; Lienenberg, John ; Magubane, Peter ; Maritz, Nicolaas ; Motswai, Tommy ; Mphahlele, James ; Mthombeni, Peter ; etc.
Vita Art Now 1989, Johannesburg Art Gallery, Johannesburg, 1990.04.24 - 1990.06.17
boek